PERANCANGAN HOTEL RESORT DI PANTAI MOMONG ACEH BESAR - ade miskarana (Universitas Syiah Kuala, 2020)
Indonesia is one of the country that has a very promising natural charm, one of it is in the province of Aceh. The beauty of natural panorama on the islands in Aceh is the attraction for tourists, one of the destination is the beaches located in the district Lhoknga. A lot of tourists who visit the beaches located in Lhoknga can be the source to developed Hotel Resort Resort as one form to increase the regional income. Design of Hotel Resort is in Momong Beach located in Lhoknga Aceh Besar, its presence is still rarely known by the crowds because the beach is covered by hills and trees around it. But the charm of this beach is very promising and spoil the eyes of visitors. Various facilities provided are expected to meet the needs of visitors to fill the time off. The theme taken is modern tropical architecture so that visitors can still feel the richness and natural beauty, without having to damage the environment around it.